Cognitive Loading During and After Continuous Task Execution Alters the Effects of Self-Controlled Knowledge of Results - Woodard, Kaylee F.; Fairbrother, Jeffrey T. (Frontiers in Psychology, 2020)
Previous research has repeatedly demonstrated that providing learners with self-control over their feedback schedules enhances motor skill learning. Increased information processing under self-control conditions has been shown to contribute to these benefits. However, the timing of critical information processing for self-control participants during the acquisition of continuous tasks is unknown. The present study was designed to enhance clarity related to this issue. Participants learned a continuous tracing task under self-control (SC) or yoked (YK) conditions. Groups of participants also completed a secondary cognitive load task either during or after the execution of each primary task trial. Results showed enhanced learning for SC compared to YK participants who did not complete the cognitive load task. However, this benefit was eliminated for SC participants who completed the cognitive load task either during or after the primary task. These findings suggest that effective information processing both during and after continuous task execution is critical for reaping the benefits of self-controlled practice. Further interpretations and implications of these findings as well as suggestions for future research are discussed.